Numerical Simulation of Jet Behavior and Impingement Characteristics of Preheating Shrouded Supersonic Jets - WEI, Guang-sheng; ZHU, Rong; CHENG, Ting; ZHAO, Fei (Journal of iron and steel research, international, 2016)
As a novel supersonic jet technology, preheating shrouded supersonic jet was developed to deliver oxygen into molten bath efficiently and affordably. However, there has been limited research on the jet behavior and impingement characteristics of preheating shrouded supersonic jets. Computational fluid dynamics (CFD) models were established to investigate the effects of main and shrouding gas temperatures on the characteristics of flow field and impingement of shrouded supersonic jet. The preheating shrouded supersonic jet behavior was simulated and measured by numerical simulation and jet measurement experiment respectively. The influence of preheating shrouded supersonic jet on gas jet penetration and fluid flow in liquid bath was calculated by the CFD model which was validated against water model experiments. The results show that the uptrend of the potential core length of shrouded supersonic jet would be accelerated with increasing the main and shrouding gas temperatures. Also, preheating supersonic jets demonstrated significant advantages in penetrating and stirring the liquid bath.